PI3K–mTOR Pathway Inhibition Exhibits Efficacy Against High-grade Glioma in Clinically Relevant Mouse Models - Fan Lin; Mark C. de Gooijer; Diana Hanekamp; G. Chandrasekaran; Levi C.M. Buil; Nishita Thota; Rolf W. Sparidans; Jos H. Beijnen; Tom Würdinger; Olaf van Tellingen (2016)
Purpose: The PI3K-AKT-mTOR signaling pathway is frequently activated in glioblastoma and offers several druggable targets. However, clinical efficacy of PI3K/mTOR inhibitors in glioblastoma has not yet been demonstrated. Insufficient drug delivery may limit the efficacy of PI3K/mTOR inhibitors against glioblastoma. The presence of the efflux transporters ABCB1/Abcb1 (P-glycoprotein, MDR1) and ABCG2/Abcg2 (BCRP) at the blood-brain barrier (BBB) restricts the brain penetration of many drugs.Experimental Design: We used in vitro drug transport assays and performed pharmacokinetic/pharmacodynamic studies in wild-type and ABC-transporter knockout mice. The efficacy of PI3K-mTOR inhibition was established using orthotopic allograft and genetically engineered spontaneous glioblastoma mouse models.Results: The mTOR inhibitors rapamycin and AZD8055 are substrates of ABCB1, whereas the dual PI3K/mTOR inhibitor NVP-BEZ235 and the PI3K inhibitor ZSTK474 are not. Moreover, ABCG2 transports NVP-BEZ235 and AZD8055, but not ZSTK474 or rapamycin. Concordantly, Abcb1a/b-/-;Abcg2-/- mice revealed increased brain penetration of rapamycin (13-fold), AZD8055 (7.7-fold), and NVP-BEZ235 (4.5-fold), but not ZSTK474 relative to WT mice. Importantly, ABC transporters limited rapamycin brain penetration to subtherapeutic levels, while the reduction in NVP-BEZ235 brain penetration did not prevent target inhibition. NVP-BEZ235 and ZSTK474 demonstrated antitumor efficacy with improved survival against U87 orthotopic gliomas, although the effect of ZSTK474 was more pronounced. Finally, ZSTK474 prolonged overall survival in Cre-LoxP conditional transgenic Pten;p16Ink4a/p19Arf;K-Rasv12;LucR mice, mainly by delaying tumor onset.Conclusions: PI3K/mTOR inhibitors with weak affinities for ABC transporters can achieve target inhibition in brain (tumors), but have modest single-agent efficacy and combinations with (BBB penetrable) inhibitors of other activated pathways may be required. Clin Cancer Res; 23(5); 1286-98. ©2016 AACR.